COEFFICIENTS OF ENERGY AND NUTRIENT APPARENT DIGESTIBILITY OF THREE RAW AND COOKED ALTERNATIVE PLANT INGREDIENTS FOR Colossoma macropomum AND Piaractus brachypomus (SERRASALMIDAE) - CHU-KOO, Fred William (2016)
The coefficients of the apparent digestibility for dry matter, crude protein, crude lipid and gross energy in cooked and raw green plantain meal (GPM), cassava root meal (CRM), and peach palm meal (PPM) were determined for juveniles of black pacu (60.8 ± 6.4 g) and red pacu (76.3 ± 5.0 g). The ADC of each alternative ingredient was determined by comparison of the digestibility (based on recovery of 1% chromic oxide as an inert marker) of a reference diet (consisting of 70% of test diet and 30% of the feedstuff) against with a test diet (24.5% of crude protein). Fish were bred in a recirculation system including 42, 110-L glass aquaria (21 tanks per species) at a density of five fish per tank, and fed their respective diets to apparent satiety, twice a day. Feces were collected after 10 days in plexiglass fecal collectors. Apparent digestibility coefficients of crude protein, crude lipid and gross energy from raw and cooked GPM and CRM were low compared to values to other common vegetal ingredients like corn and wheat. Conversely, ADC values for raw and cooked PPM were, in most cases, higher than those reported in raw or cooked GPM and CRM. In comparison with other traditional feedstuffs, apparent utilization of PPM was similar to corn and higher than reported for soybean meal and wheat bran in these fish species. Peach palm meal appears to have good potential as a feed ingredient in low-cost diets for pacu species.